Mathematics Pedagogical Content Knowledge (MPCK) in Elementary School Teachers: Focusing on Fractions - Vina Amilia Suganda M; Tatang Herman; Babang Robandi (Universitas Negeri Makassar, 2026)
Mathematics Pedagogical Content Knowledge (MPCK) needs to be developed to achieve effective learning outcomes. This study aims to describe the teaching behavior of elementary school teachers with MPCK category on fraction material in grade IV. This study used descriptive research design. The research sample is five elementary school teachers, who were randomly selected from teaching videos that have been published on YouTube. The videos of five teachers discuss the same material, namely fractions worth. The MPCK component focused on in this study is when teachers implement learning. The results of the analysis obtained the average MPCK component implemented and appropriate by the five teachers was 34%, including the category of less. From these results, the components of teaching problem solving strategies and understanding the concept of fraction material to students are the most components that are not implemented or implemented but not appropriate.